2021
DOI: 10.1038/s41398-021-01206-z
|View full text |Cite
|
Sign up to set email alerts
|

Mild behavioral impairment and its relation to tau pathology in preclinical Alzheimer’s disease

Abstract: Mild behavioral impairment (MBI) is suggested as risk marker for neurodegenerative diseases, such as Alzheimer’s disease (AD). Recently, pathologic tau deposition in the brain has been shown closely related to clinical manifestations, such as cognitive deficits. Yet, associations between tau pathology and MBI have rarely been investigated. It is further debated if MBI precedes cognitive deficits in AD. Here, we explored potential mechanisms by which MBI is related to AD, this by studying associations between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 38 publications
8
106
1
Order By: Relevance
“…We found impulse dyscontrol domain to be the most strongly associated with MTL atrophy. This complies with a very recent finding that impulse dyscontrol was associated with tau deposition in the ERC and hippocampus in preclinical AD ( Johansson et al, 2021 ). Also, an ADNI machine learning study found that baseline presence of these symptoms was an important input feature for cognitive category classification (CN, MCI, and dementia) at 40 months ( Gill et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found impulse dyscontrol domain to be the most strongly associated with MTL atrophy. This complies with a very recent finding that impulse dyscontrol was associated with tau deposition in the ERC and hippocampus in preclinical AD ( Johansson et al, 2021 ). Also, an ADNI machine learning study found that baseline presence of these symptoms was an important input feature for cognitive category classification (CN, MCI, and dementia) at 40 months ( Gill et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are therefore consistent with prior reports describing MBI as a manifestation of neurodegeneration ( Ismail et al, 2016 ) and, in some, a manifestation of early AD. The latter is also supported by research linking MBI to AD pathology in cognitively normal older adults ( Lussier et al, 2020 ; Johansson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 75%
“…A recent study found that MBI scores were associated with global and striatal amyloid-PET signal, but not with tau-PET signal [11]. Conversely, another study showed that MBI scores were associated with higher tau-PET signal in the entorhinal cortex/hippocampus [10]. This discrepancy could be attributed to diverse populations.…”
Section: Introductionmentioning
confidence: 95%
“…Two five-year longitudinal follow-up studies reported that about 70% of patients with MBI eventually progressed to dementia and MBI patients with MCI were more likely to develop Alzheimer's dementia (AD), whereas MBI patients without MCI were more likely Ivyspring International Publisher to convert into frontotemporal dementia(FTD) [4,8]. Lately, some biomarkers of neurodegenerative disease including neurofilament light [9], tau [10], and amyloid [11]; and genetic risk for AD [12] in cognitively normal samples were found to associate with MBI. A recent study found that MBI scores were associated with global and striatal amyloid-PET signal, but not with tau-PET signal [11].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the features of MCD differ from those of singledomain aMCI and of multiple-domain aMCI, which was thought to be characterized by deficits in episodic memory and one or more other cognitive domains [19]. Moreover, the MCD criteria do not correspond with those of mild behavioral impairment (MBI) which is characterized by persistent behavioral symptoms in late life and is thought to constitute a risk for neurodegenerative disease [34,35]. Indeed, in our study the MCD group did not display any behavioral or social dysfunctions.…”
Section: Mild Cognitive Dysfunctions (Mcd) As An Intermediate Classmentioning
confidence: 99%